Ubuntu as a valued capability for university students in South Africa (Journal of Student Affairs in Africa, 2023)
Universities are often described as institutions that can promote the wellbeing of their local populations. This is because they are central for advancing human development aims which support the aspirations of students and the communities from which they come. Nevertheless, we know this potential can be constrained by historical processes of oppression and negation of indigenous ways of being and doing. Applying the Capabilities Approach and Human Development paradigm as a normative framework for the outcomes of university education in the South African context, we argue for a focus on the centrality of capabilities (real freedoms) in assessing how well universities are doing to support student wellbeing. We pay special attention to one capability which we see as architectonic for other freedoms, which is Ubuntu. While Ubuntu is generally understood as a moral philosophy, in this paper we articulate it as a valued capability in the space of higher education. We also argue that it is a capability that has transformative and decolonial potential that can enable universities to promote student wellbeing if the conditions to practice it are in place.Drawing from data collected through qualitative and participatory approaches in two longitudinal research projects that were carried out between 2016 and 2021 with undergraduate students in diverse universities in South Africa, we show that Ubuntu informs students’ conceptions of humanity and their aspirations for ‘a good life’ and that it can inform the vision of transformed and decolonised university spaces that reflect indigenous ways of being and indigenous ways of seeing the world.
Keywords: Ubuntu; Capabilities; Higher Education Transformation; South Africa